Cultural diplomacy of small state’s foreign policy: A case study on Oman - Fadhil Alsaadi, Alaya Amur (2018)
Since 1970, there was a distinct feature in Oman’s foreign policy which includes moderation, pragmatism and independence. This policy was first started when Sultan Qaboos ascended the throne replacing his father Said Bin Taimur. The political turmoil and economic decline in the Middle East affected all aspects of life in Oman including its diplomatic relations. Oman is keen to exploit its cultural diplomacy to build bridges of communication and open wider channels of international cooperation with most of the states in the world. This approach is an opportunity for Oman to emerge positively and integrate with the world in order to keep abreast with the development in the global community. Thus, the political objectives that Oman aspires to achieve will be through the cultural diplomacy. This study is designed to examine to what extent the soft power has been embedded in Oman’s cultural diplomacy and what strategies were implemented in the conduct of its foreign policies. This study adopted qualitative method in data collection and analysis of both primary and secondary data. Primary data collection activities included in-depth interviews with seven respondents who are expert in the field. In addition, this study also utilized secondary data from available published documents such as books, journals, magazines and newspapers. Data transcriptions were coded and analyzed following an inductive thematic approach. Results indicate that the Omani cultural diplomacy is closely linked to Omani identity and politics. Cultural Attachés, cultural tourism, educational exchanges, cultural institutions, and the promotion of Omani cultural heritage through media are among the most important aspects of Omani cultural diplomacy. The study concludes that cultural diplomacy in the midst of political and economic crises is an important tool of Oman's international relations. Nevertheless, Oman faced a lot of challenges in the region and the world. There is growing interest from the Omani government at present in applying various types of cultural diplomacy to develop its political relations as well as to develop the state's economy. In addition, Oman seeks to preserve its cultural heritage by highlighting and sharing it with other states.